Assessment of the quality of compounded fluconazole capsules marketed in the region of Araraquara (SP, Brazil) - Josilene Chaves Ruela Corrêa; Nathália Maia Vanzela; Taízia Dutra Silva; Cristina Duarte Vianna-Soares; Hérida Regina Nunes Salgado (São Paulo State University (UNESP), 2014)
The quality control of drugs has an important role in public health, in ensuring the efficacy and safety of medicines. In the public health system, compounding pharmacies play a vital part. They provide medicines tailored to the individual patient, for example dermatological products and specific doses for children. Unfortunately, many cases of compounded products falling below the minimum quality standard have been reported in Brazil. In this study, the quality of compounded 150 mg fluconazole capsules was assessed and the results were compared with values stipulated in the Brazilian pharmacopoeia. The results suggest that, while it is certainly possible to prepare products meeting pharmacopoeial specifications, there are pharmacies where the quality control is deficient or nonexistent. Fluconazole is an important drug in combatting fungal infections. The use of fluconazole in dosage forms manufactured without high standards of quality control is strongly linked to treatment failure and cases of intoxication, as well as the emergence of resistant microorganisms. This highlights the urgent need for process improvement in compounding pharmacies. There are validated methods that can be successfully employed for routine quality control analysis that can be implemented by any compounding pharmacy.